Selection Area of Wastewater Management System Priority (Study On Sinjai District) - Dirman, Eris Nur; Sholihah, Qomariyatus; Semedi, Bambang; Solimun, Solimun; Harahab, Nuddin; Rachmansyah, Arief (Postgraduate School of Universitas Brawijaya, 2022)
The SDGs target to ensure availability and sustainable management of water and sanitation for all is related to the government's commitment through medium term development plan (RPJMN) 2020-2024, which target of 90% improved sanitation, 15% safely managed and 0% open defecation (OD). The gap between the RPJMN target and wastewater conditions in 2020 is an important problem in Sinjai district. This study aims to achieve a priority area for domestic wastewater management in Sinjai district by analyzing population density and gap analysis between wastewater conditions in 2020 and the RPJMN target gradually. Analysis data of wastewater condition and the target shows the gaps to be closed by government. The results of the analysis show that in Sinjai district there is open defecation gap of 3.68 %, improved wastewater facilities gap of 7.59%, and safely managed wastewater facilities gap of 14.15%. The selection area of domestic wastewater management system priority from the gap analysis is Pulau Sembilan sub-district with a density of 157.52 people/ha, an open defecation gap of 29.51%, improved wastewater facilities gap of 24,11%, safely managed wastewater facilities gap of 15.00%. The wastewater treatment system option based on this analysis result is Centralized Wastewater Treatment System (CWTS). Keywords: wastewater, management, sanitation, open defecation, improved, safely managed